Risk factors for antimicrobial-resistant Enterobacterales in dogs: a systematic review - Karalliu, Esa; Chung, Kai Yeung; MacKinnon, Brett; Haile, Belete; Beczkowski, Pawel M.; Barrs, Vanessa R.; Elsohaby, Ibrahim; Nekouei, Omid (Frontiers in Veterinary Science, 2024)
Identifying risk factors associated with the carriage of antimicrobial-resistant (AMR) bacteria in dogs is crucial to understanding their epidemiology and for developing and refining targeted control measures. However, relevant data is scattered and conflicting findings have been reported. This systematic review aimed to compile risk factors associated with the carriage of AMR-Enterobacterales in dogs worldwide and to identify relevant knowledge gaps for directing future research. A systematic review was conducted according to PRISMA guidelines, searching PubMed, CABi, and Scopus databases for studies reporting risk factors for acquiring AMR-Enterobacterales in dogs. After screening peer-reviewed, English-language studies by title/abstract, eligible studies were subjected to a full-text assessment, data extraction, risk-of-bias assessment, and qualitative synthesis. In the initial search, 774 articles were identified, including 274 duplicates. After screening by title/abstract, 77 articles were subjected to full-text review, from which 40 were eventually selected for data extraction, including 29 cross-sectional, six cohort, and five case-control studies. The most frequently investigated risk factors for AMR-Enterobacterales carriage in dogs were antimicrobial use (28 of 40), age (24), sex (22), hospitalization (19), and feeding raw diet (14). Of these, antimicrobial use was the most common risk factor significantly associated with AMR-Enterobacterales (19/28), followed by raw diet (9/14) and hospitalization (8/19). Our synthesis emphasized the importance of increasing awareness regarding the prudent use of critically important antimicrobials (CIAs), such as fluoroquinolones, in companion animal practices, strengthening infection prevention and control procedures in veterinary clinics and hospitals and educating caregivers about the potential risks of feeding raw diets in order to reduce the burden of AMR-bacteria in dogs.